Peran Badan Ansor Anti Narkoba (BAANAR) dalam Menanggulangi Peredaran Narkoba di Pamekasan - Syarif, Zainuddin (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2019)
The results of this study reveal the meaning of the role of Ansor Anti-Narcotics Agency (BANAAR) behind the phenomenon of drug trafficking in the middle of many pesantren, especially in East Java Pamekasan Regency, where this area is in the midst of society which can be considered advanced in terms of education. From year to year, the drug density is increasingly showing its intensity. Based on data from the Pamekasan District Narcotics Board (BNK) showing that in the period of almost 2016, it increased to 15.69 percent if we compare the same case during 2015. There are at least four (4) points of significance from the results of this study which among others: 1) this study describes prevention pattern BANAAR cooperate with pesantren to drug distribution in Pamekasan Regency. 2) to find strategies and approaches undertaken by BANAAR in collaboration with BNK and the police who are persuasive refresif so that the circulation of narcotics can be minimized. 3) the role of BANAAR in guarding the flow of technological development, because technology is part of an important factor in pengidaran so that the level of drug problems in Indonesia is also increasing. 4) recommendations to BANAAR, as it has to prepare more mature and more seriously on the planning of targeted, effective, efficient and professional programs in the prevention of drug trafficking.